(untitled) (Journal of the College of Education for Women, 2023)
Ecolinguistics is a twofold field in which ecology and language are its two major concerns. That is, this field is concerned with the way through which our thoughts, ideologies and the like influence the environment. The present study aims at analyzing (6) constructive and destructive environmental advertisements to find out how the techniques of erasure and salience operate in these types of advertisements. It studies the linguistic expressions that achieve these techniques in the constructive and destructive advertisements. The qualitative and quantitative methods are exploited in the current study. Analyzing (6) constructive and destructive environmental advertisements in accordance with Stibbe’s (2015) model of salience and erasure accomplishes the qualitative approach whereas accounting the frequencies and percentages of salience and erasure occurrences in constructive and destructive environmental advertisements accomplishes the quantitative approach. The model of the analysis used in the present study is of Stibbe’s (2015) theory of erasure and salience. The main finding shows that the technique of salience is employed more frequently in constructive advertisements than that of erasure, whereas the same techniques are equally used in destructive advertisements. The main conclusion of the present study reads that the technique of salience is appropriate for constructive advertisements since it highlights the important aspects of the environmental advertisements